2018
DOI: 10.1037/cfp0000108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship satisfaction and mental health treatment among active-duty military.

Abstract: An association between relationship satisfaction and mental health symptoms has been well established in research. Specifically, mental health concerns, such as trauma symptoms and depression, have been related to lower relationship satisfaction. Research has explored the correlation between relationship satisfaction and mental health symptoms during treatment but not among active-duty military and not examining a between-person and within-person effect. Therefore, the present study investigates these variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…This is confirmed by previous research on relationship uncertainty which found that individuals who are more certain about their relationships have higher levels of commitment to the relationship and engage in more behaviors to maintain the relationship [20]. Overall, a considerable amount of research links mental health to romantic relationship outcomes [21][22][23]. Investigating whether there is a similar link between disorder symptoms when comparing individuals in committed, monogamous relationships versus individuals in non-committed, non-monogamous relationships can provide additional insight into interpersonal functioning.…”
Section: Introductionsupporting
confidence: 76%
“…This is confirmed by previous research on relationship uncertainty which found that individuals who are more certain about their relationships have higher levels of commitment to the relationship and engage in more behaviors to maintain the relationship [20]. Overall, a considerable amount of research links mental health to romantic relationship outcomes [21][22][23]. Investigating whether there is a similar link between disorder symptoms when comparing individuals in committed, monogamous relationships versus individuals in non-committed, non-monogamous relationships can provide additional insight into interpersonal functioning.…”
Section: Introductionsupporting
confidence: 76%
“…Among active-duty Army couples, PTSD symptoms were associated with higher concurrent marital distress for both spouses (Allen, Rhoades, Stanley, & Markman, 2010), and returning from deployment with PTSD symptoms predicted an increase in subsequent divorce likelihood of 10 -20% among soldiers and 50 -75% among officers (Negrusa & Negrusa, 2014). Linear growth curve analyses of changes in relationship distress and PTSD symptoms in active-duty service members undergoing individual mental health treatment have suggested that the longitudinal association between relationship distress and PTSD symptoms is a function of a within-individual process (i.e., participants' individual-level deviation from their own average relationship satisfaction scores, reflecting that individuals with positive change in their marriages over the course of treatment experienced greater reductions in PTSD symptoms than would otherwise be predicted; Edwards-Stewart et al, 2018).…”
mentioning
confidence: 99%
“…This finding reinforces the necessity of assessing and addressing IPV directly, as it may be a key stressor among service members who are in relationships and at high risk for self-harm. Attending to relation-ship satisfaction, safety, and longevity may promote mental health among active duty military (Edwards-Stewart et al, 2018).…”
Section: Discussionmentioning
confidence: 99%